2019
DOI: 10.3390/ijerph16030506
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Pathogen Diversity in Infant Foods in Low-Income Neighborhoods of Kisumu, Kenya

Abstract: Pediatric diarrheal disease remains the second most common cause of preventable illness and death among children under the age of five, especially in low and middle-income countries (LMICs). However, there is limited information regarding the role of food in pathogen transmission in LMICs. For this study, we examined the frequency of enteric pathogen occurrence and co-occurrence in 127 infant weaning foods in Kisumu, Kenya, using a multi-pathogen PCR diagnostic tool, and assessed household food hygiene risk fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…• understood, high pathogen prevalence in food in Kenya (Tsai et al, 2019) raises concern that enteric pathogens may occur at higher than acceptable rates in child foods in this population.…”
Section: Storage After Feedingmentioning
confidence: 99%
“…• understood, high pathogen prevalence in food in Kenya (Tsai et al, 2019) raises concern that enteric pathogens may occur at higher than acceptable rates in child foods in this population.…”
Section: Storage After Feedingmentioning
confidence: 99%
“…In many low-and middle-income countries (LMIC), complementary foods given to infants during the critical weaning period can be highly contaminated, [1][2][3] and contaminated weaning foods are a neglected source of enteric pathogen exposure. 4 Complementary food hygiene interventions have shown significant reductions in infant food contamination and improved behaviors.…”
mentioning
confidence: 99%
“…Storing complementary foods for extended periods of time at ambient temperatures is associated with increased bacterial contamination, especially in tropical climates such as those in East Africa. 3 Infant food was prepared in parallel with food preparation for the larger family and timing determined by caretaker's economic responsibilities outside of the home. Because of employment demands and reliance on charcoal and paraffin stoves, reheating food-a common behavioral target for food hygiene interventions 1,2,5 -requires time and economic resources that families do not have.…”
mentioning
confidence: 99%
“…Food is likely to be an important source of exposure to enteric pathogens in early childhood. Recent studies have shown that food given to children in early childhood can be highly contaminated with faecal indicator bacteria [5] as well as specific diarrhoeagenic enteric pathogens [6]. Environmental interventions to reduce exposure to these pathogens and reduce diarrhoea have traditionally focused on improving the quality and distribution of drinking water, the management of excreta through sanitation systems and the promotion of handwashing with soap at critical times [7] but generally not on food hygiene related behaviours and infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Although access to safe water and sanitation is generally higher in urban areas [9], the risk of enteric infection may be greatest in poor urban areas due to the combination of high population density and limited public health infrastructure [10–13]. These conditions pose multiple risks for contamination of food as supported by a recent study of pathogen diversity in infant food in low-income informal neighbourhoods of Kisumu, Kenya [6]. The ‘Safe Start’ trial is designed to assess whether a locally appropriate, low-cost food hygiene intervention, delivered within the context of the existing health extension system in peri-urban neighbourhoods of Kisumu, Kenya can reduce early childhood exposure to enteric pathogens.…”
Section: Introductionmentioning
confidence: 99%